Helminthes in carnivorous mammals in Central Black Earth Nature Reserve - E. A. Vlasov; N. S. Malysheva; N. A. Vagin; N. A. Samofalova; N. A. Samoylovskaya; E. I. Malakhova; V. V. Gorohov (Российский паразитологический журнал)
Helminthological studies of carnivores in Central Black Earth Nature Reserve (Kursk region) are carried out. High degree of infection of carnivores with hel-minthes is determined. Helminth eggs have been detected in 98 % of animal fecal samples. More often eggs of cestodes, nematodes Capillariidae, Tosascaris leoni-na, Uncinaria stenocephala, trematodes Alaria alata have been found. In 94,1 % of foxes a mixed infection caused by A. alata, Capillaria spp., T. leonina, Toxocara sp., U. stenocephala and cestodes has been determined. Carnivores of martens fam-ily were infected with Capillaria spp. and cestodes. 4,9 % of foxes were infected with one helminth species. The most common helminthes in carnivores are Capil-laria spp. High density of carnivores in nature reserve may cause widespread hel-minthosis.